Photosynthetic Performance and Vegetative Growth in a New Red Leaf Pear: Comparison of Scion Genotypes Using a Complex, Grafted-Plant System - Tozzi, Francesca; van Hooijdonk, Ben M.; Tustin, Donald S.; Corelli Grappadelli, Luca; Morandi, Brunella; Losciale, Pasquale; Manfrini, Luigi (Frontiers in Plant Science, 2018)
Leaf photosynthetic performance of a new red-skinned inter-specific hybrid pear variety called PREMP009 (PIQA®BOO®) is presently unknown and therefore was compared to the Asian pear variety Hosui. The seasonal growth patterns and the final dry matter accumulation of all tree part components were also investigated for both genotypes in their first year of growth after grafting. Leaf gas exchange and tree growth comparisons were assessed using an innovative grafted plant system, which involved a bi-axis tree with the presence of combinations of identical or mixed (one of each genotype) ‘PREMP009’ and ‘Hosui’ scion genotypes grafted onto a single clonal rootstock (‘Buerre Hardy’ BA29). This experimental grafted plant system allowed a technique for comparing leaf photosynthesis of two scion genotypes on the same root system, thereby avoiding between-plant differences in plant water relations. ‘PREMP009’ had higher leaf photosynthesis and higher leaf mass area compared with ‘Hosui’. However, by the end of the first year of growth, primary shoots of ‘PREMP009’ were shorter with fewer nodes, corresponding to less dry weight gain in primary shoot leaves and stems. This vegetative behaviour of ‘PREMP009’ is likely a response to the smaller individual leaf area in early season affecting light capture that greatly limits dry matter accumulation of young trees.